Hubungan Tingkat Pengetahuan Orang Tua dengan Status Karies Gigi Siswa Usia 10–12 Tahun di SDN Talawaan Bajo Kabupaten Minahasa Utara - Mariati, Ni Wayan; Mintjelungan, Christy N.; Vania, Marella T. (Universitas Sam Ratulangi, 2025)
Abstract: Dental caries is most commonly caused by demineralization, namely loss of the structure of the hard tooth tissue which consists of email, dentine, and cementum. Dental caries has several causative factors, one of which is knowledge which is an external factor in the occurrence of dental caries. This study aimed to determine the relation between the level of parental knowledge and the dental caries status of students aged 10–12 years at SDN Talawaan Bajo, North Minahasa Regency. This was an analytical and descriptive study using a cross-sectional design. Samples consisted of students aged 10–12 years and parents of the students, totaling 42 people each, who were taken by total sampling technique that met the inclusion criteria. The results showed the parental levels of knowledge about caries, categorized as follows: good (95.24%), moderate (4.76%), and poor (0,0%). Dental caries status of students aged 10–12 years with very low (35.71%), low (21.43%), moderate (26.19%), high (9.52%), and very high (7.14%). The Spearman Rank test showed a p-value of 0.38 (>0.05). In conclusion, there is no significant relation between the level of parental knowledge and the dental caries status of students aged 10–12 years at SDN Talawaan Bajo, North Minahasa Regency. Keywords: caries status; parental knowledge; students Abstrak: Karies gigi paling sering terjadi akibat demineralisasi yaitu hilangnya struktur dari jaringan keras gigi yang terdiri dari email, dentin, dan sementum. Karies gigi memiliki beberapa faktor penyebab, salah satunya ialah pengetahuan yang merupakan faktor eksternal timbulnya karies gigi. Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan orang tua dengan status karies gigi siswa usia 10–12 tahun di SDN Talawaan Bajo Kabupaten Minahasa Utara. Jenis penelitian ini ialah deskriptif analitik dengan desain potong lintang. Sampel penelitian terdiri dari siswa berusia 10–12 tahun dan orang tua siswa yang berjumlah masing-masing 42 orang, diambil dengan teknik total sampling yang telah memenuhi kriteria inklusi. Hasil penelitian memperlihatkan bahwa tingkat pengetahuan orang tua tentang karies dengan kategori baik (95,24%), kategori sedang (4,76%), dan kategori kurang (0,0%). Status karies gigi siswa usia 10–12 tahun dengan kategori sangat rendah (35,71%), rendah (21,43%), sedang (26,19%), tinggi (9,52%), dan sangat tinggi (7,14%). Hasil uji Spearman Rank menunjukkan nilai p=0,38 (0,38>0,05). Simpulan penelitian ini ialah tidak terdapat hubungan bermakna antara tingkat pengetahuan orang tua dengan status karies gigi siswa usia 10–12 tahun di SDN Talawaan Bajo Kabupaten Minahasa Utara. Kata kunci: status karies; tingkat pengetahuan orang tua; siswa